Stroboscopic eyewear applied during warm-up does not provide additional benefits to the sport-specific reaction speed in highly trained table tennis athletes - Strainchamps, P.; Ostermann, M.; Mierau, A.; Hülsdünker, T. (International Journal of Sports Physiology and Performance, 2023)
Purpose: While long-term training with stroboscopic eyewear suggests performance-enhancing effects on visuomotor abilities, it remains unclear whether a short-term application, for example, during a warm-up, results in immediate performance gains. This study evaluated potential performance-enhancing effects of stroboscopic eyewear applied during warm-up on reaction speed that may provide athletes an edge in visuomotor-demanding sports.